2010
DOI: 10.1080/07347331003689052
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Blame for Breast and Lung Cancers in Women

Abstract: Breast cancer is the second most common cancer in American women, and lung cancer is the deadliest. The etiology of breast cancer is not clear, although 85% of lung cancers are explained by cigarette smoking. A research review of the social perception of serious illness has shown that causal explanations fall into two categories: (1) patient behavior and (2) factors outside the patient's control. Presented in this review are questions concerning (1) patient coping, (2) stigma, and (3) the responses of the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
21
0
3
Order By: Relevance
“…Additionally, spouses who never smoked were more likely to blame the patient compared to those with a personal smoking history. Consistent with previous work (9-11), we demonstrated that attributions of blame at treatment initiation are harmful because they are associated with increased initial distress in patients and even more so in spouses. Our hypothesis regarding moderators (i.e., dyadic adjustment, network support) of the association between blame and distress was partially supported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, spouses who never smoked were more likely to blame the patient compared to those with a personal smoking history. Consistent with previous work (9-11), we demonstrated that attributions of blame at treatment initiation are harmful because they are associated with increased initial distress in patients and even more so in spouses. Our hypothesis regarding moderators (i.e., dyadic adjustment, network support) of the association between blame and distress was partially supported.…”
Section: Discussionsupporting
confidence: 91%
“…Because at least 80% of lung cancers are linked to a history of poor health behaviors particularly smoking (8), patients may blame themselves for developing cancer, which may contribute to or exacerbate their psychological distress. In fact, a few studies have demonstrated that lung cancer patients are more vulnerable to blaming themselves (9-11) for developing cancer compared to other cancer populations including breast and prostate cancer patients whose illness etiology is less lifestyle dependent (11-13). Nevertheless, it is unclear if lung cancer patients who have a history of smoking are actually more vulnerable to attributions of blame compared to never smokers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast cancer story teaches us that attitudes on cancers can change 23. Breast cancer was once highly stigmatized and rarely discussed in public.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer patients are more likely than breast and prostate cancer patients to report internal causal attributions for their cancer [83,84]. Within the past 20 years, cancer patient populations, such as breast cancer patients, have received greater sympathy and social awareness [85], but lung cancer patients are less likely to receive sympathy and support.…”
Section: Lung Cancer and Stigmamentioning
confidence: 99%